EFFECT OF SODIUM SILICATE TO SODIUM HYDROXIDE RATIOS ON DURABILITY OF GEOPOLYMER MORTARS CONTAINING NATURAL AND ARTIFICIAL POZZOLANS - F. Nurhayat Degirmenci (Ceramics-Silikáty, 2017)

(untitled)
This study aims to provide the experimental data on the sulphate and acid performance of geopolymer mortar containing pozzolanic materials such as fly ash (FA), ground granulated blast furnace slag (GGBS) and natural zeolite (NZ). The alkaline solution was the combination of sodium silicate and sodium hydroxide solution with the ratio (Na ₂SiO₃/NaOH) of 1.0, 2.0 and 3.0. The molarity of sodium hydroxide was fixed as 10. The performances of geopolymer mortar were measured in terms of sodium and magnesium sulphate resistance and sulphuric and hydrochlorich acid resistance with 5% and 10 % concentration after 24 weeks. The evaluations were measured as visual observation, measurement of weight change and residual compressive strength. It has been observed that Na ₂SiO₃/NaOH ratio is effective on residual compressive strength of geopolymer mortar in both sulphate and acid exposure. The higher ratio of Na ₂SiO₃/NaOH results in a higher residual compressive strength. The GGBS based geopolymer mortar has a very good resistance in acid media in terms of weight loss and residual compressive strength. The inclusion of FA in the GGBS based geopolymer mixture was found to be a suitable base of geopolymer mortar under ambient curing conditions.